User-centered water and pasture monitoring and early warning system for conflict management in pastoral areas of Ethiopia - Dejene, Sintayehu W.; Alemayehu, Sintayehu; Tegegne, Getachew; Yodit, Y.; Tesfaye, Lidiya; Terefe, Tadesse; Gebre, Liyuneh (2025)
The Livestock Water Monitoring and Risk Management System (LWMRMS) Project, implemented by the Alliance of Bioversity International and CIAT in collaboration with various Ethiopian institutions and supported by the Gates Foundation, addresses challenges in sustainable pastoral development, climate change-induced risks, and resource-based conflicts. The project developed the ET-Monitoring platform, a web-based digital tool providing real-time water and pasture data in multiple languages. This platform helps pastoralists and stakeholders make informed decisions on livestock movement, reducing competition over resources and minimizing conflict risks. ET-Monitoring promotes sustainable resource use by guiding strategic grazing and watering practices, preventing overgrazing, and ensuring ecosystem health. It also supports data-driven conflict prevention and mediation by empowering local authorities and communities with evidence-based tools. The system contributes to peacebuilding, enhances cooperation, and aids crisis response planning for humanitarian agencies. Expanding ET-Monitoring to other pastoral regions will further strengthen pastoral resilience, reduce climate and resource-induced conflicts, and promote sustainable resource management across Ethiopia.